Enhancing EFL Young Learners"™ Writing Proficiency Through Local Content: A Classroom Action Research - Dwimaulani, Astrid; Setiawan, Budi; Risviana, Risviana (Journal of English Education Program, 2025)
This study aims to explore the effectiveness of implementing local content in developing EFL learners"™ descriptive text writing skills. The approach used in this study was classroom action research. The steps taken in this classroom action research were planning, action, observation, and reflection. The research process utilized two cycles. In the first cycle, students"™ descriptive writing skills were assessed. After a period of instruction using this approach, a post-assessment was conducted to measure students"™ improvement in writing skills. The test scores were then analyzed using a percentage formula. Only 38% of the students were in the "good" category in the first cycle. However, in the second cycle, there was a significant increase of 73% after the implementation of local content in the writing learning process. The use of local content makes students more interested and enthusiastic in developing their ideas, so that they are more creative in describing existing material. Therefore, students are automatically more passionate about learning new vocabulary and deepening their grammatical understanding. It can be concluded that teaching descriptive texts to young EFL learners using local content can improve their writing proficiency.